Contingencies in Behavioral Mode : Enhancing Player's Adaptive Ability. (December 2020) - Liu, Febyola Vanessa; Rohizan, Rizawati; Tan, David; Chen, Tet-Khuan
Abstract: Metamorph is a stealth action RPG with bvoth open world and mission-based settings. Adopting the elements of cyberpunk and capitalistic system with immense number of AIs, this game is set in a futuristic-style city with four main districts, each with different culture and building design. The player will play as Centauri, a cyborg who joins Private Sector Resistance in order to stop the Private Sector that produces war machines which are in form of droids with artificial intelligence from colonizing the world. There is a wide range of enemy types, two gameplay styles and various game mechanics in order to complete the missions, this game focuses on player's adaptive and cognitive abilities throughout the levels.